Problem-Based Module Biodiversity Learning Materials To Improve 4c Skills - Saragih, Dina Fitriyani (Gunung Djati Conference Series, 2025)
The goal of this study is to establish whether or not the biology learning module is valid, whether or not it is practical, and whether or not it is effective in improving students' 4C biology skills. According to the ADDIE model of development, this kind of research is considered to be development research. The place and location of this research is at Al Ulum Islamic High School in Medan. The participants in this study are thirty students who are enrolled in class X at Al Ulum High School in Medan. The findings of this research indicate that the validity of the problem-based learning module, which is based on the problem-based model, is included in the valid category. This means that the learning module that was developed has satisfied the validity indicators. With regard to the students' 4C skills, the practicality of the problem-based learning module is included in the category of practical. Based on the problem-based model, the effectiveness of the problem-based learning module for students' 4C skills is sufficient to meet the effectiveness criterion.